PENGARUH PENAMBAHAN SERAT RAMI DAN BATANG PISANG TERHADAP KEKUATAN IMPAK DAN FLEKSURAL BASIS GIGI TIRUAN AKRILIK - Endang Prawesthi; Marzia M Tetelepta; Heldayani Heldayani (B-Dent: Jurnal Kedokteran Gigi Universitas Baiturrahmah, 2022)
Introduction: Acrylic denture in its use often results in fractures and one of the causes is due to poor mechanical resistance, especially to impact strength. Several methods to prevent broken acrylic, include the addition of fibers that function as reinforcement. There are 2 types of fibers, synthetic and natural fibers. Synthetic fibers are relatively expensive, so an alternative is needed, namely the use of natural fibers (Ramie and banana stem). This study purposed to determine the effect of adding ramie fiber and banana stem to impact and flexural strength of acrylic denture base. Methods: Experimental Laboratory, number of 60 samples consisted of 30 samples for flexural and impact tests. The sample was an acrylic plate; size 65x10x2.5 mm for Flexural Test and 80x10x4 mm (Flatwise impact method without notched) for Impact Test. The fiber concentration added was 1.6% of the sample weight. The sample consisted of 3 groups, namely control, the addition of ramie and banana stem fibers. Flexural test with UTM and Impact test with Charpy method. Results: Flexural and impact strength mean value of the ramie fiber group had the highest value (132.7459MPa; 7.9859 x 10-3Joule/mm2), followed by the control group (99.8499MPa; 4.2757 x 10-3Joule/mm2) and smallest value was in banana midrib fiber group (91.6865MPa; 3.0303 x 10-3Joule/mm2). The LSD test of significance(p) between each group in flexural and Impact Strength tests showed a significant difference (p<0.05). Pearson correlation test showed a significant positive correlation between the two tests. Conclusion: The addition of ramie fiber can increase the impact and flexural strength of denture acrylic, but it is different from the addition of banana midrib fiber because the presence of flavonoids (phenol compounds) it contains causes a decrease in the strength of denture acrylic.